2016
DOI: 10.3851/imp3114
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Virological Suppression and Rebound between Indigenous and Non-Indigenous Persons Initiating Combination Antiretroviral Therapy in a Multisite Cohort of Individuals Living with HIV in Canada

Abstract: Lower suppression rates among Indigenous persons suggest a need for targeted interventions to improve HIV health outcomes during the first year of treatment when suppression is usually achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A study comparing African-American with European-American US military personnel found that, despite having free access to medical care and medication and similar durations of infection before diagnosis, the proportion of people obtaining viral load suppression at 6 months and 12 months after ART initiation was still 40% lower in the African-American group. 5 The data for durable viral load suppression are conflicting regarding whether minority groups or disadvantaged populations have the same 5,6 or, as was found by O'Connor and colleagues, higher 9 rates of viral rebound than non-minority populations. Notably, a growing body of data exists that shows good overall rates of viral suppression in sub-Saharan Africa.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A study comparing African-American with European-American US military personnel found that, despite having free access to medical care and medication and similar durations of infection before diagnosis, the proportion of people obtaining viral load suppression at 6 months and 12 months after ART initiation was still 40% lower in the African-American group. 5 The data for durable viral load suppression are conflicting regarding whether minority groups or disadvantaged populations have the same 5,6 or, as was found by O'Connor and colleagues, higher 9 rates of viral rebound than non-minority populations. Notably, a growing body of data exists that shows good overall rates of viral suppression in sub-Saharan Africa.…”
mentioning
confidence: 99%
“…2,3 Of note, the authors also found that black African men and women had higher rates of viral rebound, a finding that was also shown in a study investigating protease inhibitor monotherapy in the UK. 4 Lower initial rates of viral suppression after starting ART have been commonly reported in African Americans 5 and Indigenous communities in Canada, 6 but not in Aboriginal people in Australia. 7 A large study in the USA assessing racial differences in ART response from the AIDS Clinical Trials Group found that black participants had a 40% higher risk of virological This finding is perhaps surprising given the substantial attention to the notion of accelerated atherosclerosis, or even accelerated aging, in people with HIV in the past few years.…”
mentioning
confidence: 99%
“…Indigenous identity reported at ART initiation was also found to be strong predictors of viral suppression in this cohort. Findings from Benoit et al 32 not only echoed the same findings of poor viral suppression among PLWH in Canada, but also reported how younger adults who identify as Indigenous (54%) were less likely than non-Indigenous people (77%) to experience viral suppression. Indigenous women, who comprise 22% of CHIWOS participants, reported low rates of viral suppression in comparison to ACB and white women regardless of whether they lived in the GTA, in the rest of Ontario or in Quebec and BC.…”
Section: Discussionmentioning
confidence: 62%
“…Benoit et al 2017 [30] Are there differences in experiencing (1) virologic suppression and (2) virologic rebound between Indigenous and non-Indigenous people living with HIV?…”
Section: Building Bridgesmentioning
confidence: 99%